Scandinavian Iron Age and Early Medieval Ceramic Moulds - Lost Wax or Not or Both? - Anders Söderberg (EXARC Journal)
Since the 1940s we have had a discussion in Scandinavia concerning ancient mould-making methods. The question of different methods in the production of ceramic moulds has taken a large part in these discussions; by lost wax or by direct matrix-methods. This study gives a brief background to the subject and presents the results of a small series of experiments, related to questions concerning the methods used at the Migration/Merovinginan Period workshops at Helgö, Sweden. The study claims that lost wax-methods could have been used at Helgö to a larger extent than claimed earlier. This conclusion however does not exclude possible use of direct matrix-methods.